Association between early life adversity and allostatic load in girls with precocious puberty. (June 2023) - Li, Jing; Yu, Yue; Yuan, Jingyi; Liu, Deyun; Fang, Jiao; Wu, Peipei; Zhou, Yi; Wang, Ya; Sun, Ying
Abstract: Context: The mechanisms underlying the elevated long-term health risk in girls with precocious puberty remain unclear, but might result from physiological wear and tear associated with greater exposure to early life adversity. Objective: This study aims to explore early life adversity in girls with precocious puberty and its association with allostatic load. Methods: Early life adversity and hair cortisol concentration were measured among 213 girls with precocious puberty (8.21 ± 1.07). Allostatic load score is constructed by using 13 physiological biomarkers representing four systems and hair cortisol concentration. Multivariate linear regression models have estimated the associations between cumulative early life adversity exposure with total and system-specific allostatic load scores. Associations between cumulative early life adversity and the risk of high allostatic load (3 + high-risk biomarkers) were tested using binary logistics regression. Results: More than two-thirds (67.6%) of girls with central precocious puberty reported two or more early life adversity exposure. Compared to those with no early life adversity exposure, girls who reported early life adversity score ≥ 2 had significantly higher total allostatic load score ( β: 1.20–1.64, P < 0.001). Metabolic system was more sensitive to cumulative early life adversity exposure, each form of early life adversity exposure was associated with 0.48-unit increases in metabolic allostatic load score (95%CI: 0.06, 0.90, P = 0.026). Girls reported early life adversity score ≥ 3 were three times more likely to have a high allostatic load compared with those without early life adversity exposure in both unadjusted and adjusted models ( OR adjusted =3.83, 95%CI: 1.17, 12.55, P  = 0.001). Conclusion: Multisystem physiological dysregulation is observed in girls with central precocious puberty, which might result from cumulative wear-and-tear associated with early life adversity. Highlights: Allostatic load is a useful perspective for understanding higher risk for adverse outcomes in girls with precocious puberty. Moderate- and severe- cumulative early life adversity was associated with an increased allostatic load. Metabolic system was more sensitive to cumulative early life adversity exposure in girls with precocious puberty. Sheds a perspective and theoretical basis for understanding the long-term health effects of girls with precocious puberty.